CRESCIMENTO E DESEMPENHO ECONÔMICO DE Eucalyptus dunnii EM DIFERENTES SÍTIOS NO PLANALTO SUL DO BRASIL - Dobner Jr., Mário; Batista, Kamila Mesquita; Sartório, Ian Pereira; Arce, Julio Eduardo; Quadros, Dagoberto Stein (Floresta, 2017)
A busca por maior produtividade, menores ciclos de produção e, consequentemente, maior desempenho econômico tem levado empresas e proprietários rurais do Planalto Sul do Brasil a investir em plantações de Eucalyptus em detrimento de Pinus. A determinação da produtividade e do desempenho econômico de povoamentos florestais é fator básico para o planejamento e otimização do manejo destes. Nesse contexto, o presente estudo foi realizado com o intuito de avaliar o crescimento e o desempenho econômico de plantios de Eucalyptus dunnii em diferentes sítios no Planalto Sul do Brasil. Foram utilizados dados de inventário florestal contínuo, totalizando 128 unidades amostrais e 10.903 pares de dados dap x hdom. Foram obtidas três classes de sítio com alturas dominantes assim distribuídas na idade índice de 10 anos: Classe I: 34 a 39 m; Classe II: 29 a 33,9 m; Classe III: 24 a 28,9 m. Povoamentos com d200 de 30 cm podem ser obtidos já aos 9 anos de idade em sítios altamente produtivos. Entretanto, demoram de 3 a 5 anos a mais para serem obtidos em sítios menos produtivos. A taxa interna de retorno (TIR) de sítios altamente produtivos é duas vezes maior que em sítios de menor produtividade. Valor presente líquido (VPL) e valor esperado da terra (VET), no sítio de alta produtividade, são 14 vezes superiores aos observados nos piores sítios. Conclui-se não só queé mais rentável produzir E. dunnii em sítios mais produtivos, mas também que o cultivo de E. dunnii pode não ser viável em sítios pouco produtivos. Palavras-chave: Manejo Florestal; Eucalipto; Manejo para Multiprodutos. Abstract Growth and economic performance of Eucalyptus dunnii at different sites on the Highlands of Southern Brazil. The search for greater productivities, shorter production cycles and thus higher economic performances have led companies and landowners on the Highlands of Southern Brazil to invest in Eucalyptus plantations rather than Pinus. Determining the productivity and economic performance of forest stands is a key factor for their planning and management. In this context, the present study was carried out aiming to evaluate de growth and economic performance of Eucalyptus dunnii in different sites on the Highlands of Southern Brazil. Data from continuous forest inventory were regarded with a total of128 sample plots and 10.903 dbh x hdom paired values. Three site classes were obtained with dominant heights at index age of 10 years as the following: Class I: 34 to 39 m; Class II: 29 to 33,9 m; Class III: 24 to 28,9 m. Stands of d200 of 30 cm can be obtained since the age of 9 years-old on sites of high productivity, while it takes from 3 to 5 years on sites of lower productivity. The internal rate of return (IRR) on sites of high productivity is twice as high as the ones verified on sites with lower productivity. Net present values (NPV) and land expectation values (LEV) on sites of high productivity are 14 times higher than the ones observed on the worst sites. It was concluded that it is not only more profitable to grow E. dunnii on sites of high productivity, but also that there might be no viability at all of its cultivation on low productivity sites. Keywords: Forest Management; Eucalypt; Multiproducts Management.